Implementation of DMAIC for Production Quality Control: Case Study of Power Supply Production in Indonesia - Purwojatmiko, B. Handoko; Ambarwati, Laksmi (Jurnal Teknik, 2023)
The level of competition in the manufacturing industry is getting tougher, making companies must be able to provide the best service to customers. One of the companies in Indonesia engaged in asset monitoring and ship navigation systems, has a production division that produces power supply products. Based on the analysis that has been carried out at the company that there are problems such as a damaged PCB connector that makes the product categorized as a manufacturing defect. This research aims to be able to find alternative improvements to production processes that have a high defect rate. The Define, Measure, Analyze, Improve, and Control (DMAIC) framework is used as a method to shape the mindset of management and employees to be able to solve these problems. Based on this framework, three causes of the problem were found, namely human factors, materials, and inappropriate methods during the production process. Therefore, appropriate corrective actions are taken, and a control process is carried out by comparing control charts, Defects Per Million Opportunities (DPMO) and sigma levels to determine the impact of changes from the improvements made. Quantitatively, there was an increase in the DPMO value of 39.47% and an increase in the sigma level of 8.64%. This shows that the DMAIC framework can provide the right solutions and preventing the same quality problems from happening again.